Seismic design of steel structures - Köse, İsmail. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1996., 1996)
One of the most important disasters that humanity suffered throughout the history is earthquake. Although it is impossible to overcome earthquake, protection from its harms is possible by taking some precautions. Structural steel behaves the best for earthquake resistance among all structural materials, but considerable care is needed in design and detailing of framing systems. The collapse mechanism influences the energy dissipation capacity of the structure. Therefore, it plays a very important role in seismic design of steel structures. The case in which a framed structure fails according to global type mechanism can be adopted as the reference case, because it is considered to exhibit enough ductility to withstand severe earthquakes. In the thesis, a computer program is developed and verified based on the method of global mechanism in ECCS recommendations. The program is used on the structures which are preliminary designed by elastic or plastic theories. It ensures the structures to collapse at global mechanism. In the program, if the collapse mechanism of the system is different from global mechanism, the plastic moments of columns are modified by an amplification factor. Consequently, new column sections satisfying global mechanism are determined according to the increased plastic moments of columns.
Keywords: Earthquake resistant design.; Steel, Structural.